Different, not dumb - Marek, Margot; Kirk, Barbara (New York : F. Watts, 1985)
Because he gets some letters mixed up or reversed, Mike is assigned to a special class in which he learns the basic reading skills he eventually uses to avert a serious accident.
Keywords: Children$1 (Bs stories, American.s; Reading -- Fiction; Dyslexia -- Fiction; Schools -- Fiction